LITERATUR REVIEW: ANALISIS PENERAPAN PRINSIP KESELAMATAN PASIEN DALAM PEMBERIAN OBAT TERJADINYA MEDICATION EROR DI RUANG RAWAT INAP 1B MAYAPADA HOSPITAL - Retno Andriati; Ayu Rahayu; Marsondang Situmeang; Dyna Meilolita Sirait; Nurminauli, Nurminauli; Sulistyorin, Sulistyorin; Juni Novelina; Yona Riana; Rosita, Rosita; Lady Agitha; Tim IPD IB dan OPD BPJS (Nusantara Hasana Journal, 2025)
Patient Safety Goals are a requirement that needs to be implemented in all hospitals accredited by the Hospital Accreditation Commission. From the WHO’s 10 facts about patient safety in developing countries in 2023, it is stated that there are 1 in 10 patients hospitalized at risk of medical errors and errors in the administration of harmful drugs. Nurses must be skilled and precise when administering drugs, not just giving drugs, but also being able to observe the client’s response to the administration of the drug, knowledge of the benefits and side effects of the drug. Nurses in giving drugs must also pay attention to the prescription of drugs given must be precise, the right count on the dose given according to the prescription and always use the 7 correct principles. This study aim to determine the factors that influence the occurrence of medication errors. This research is literature review, articles obtained from google scholar. The results show that there are errors in the administration of patient medication, at the prescribing, transcribing, dispensing and administration stages. The conclusion is that there are errors in the administration of patient drugs that usually occur at the prescribing, transcribing, dispensing, and administration stages